Effects of Storage Temperature and Duration on the Hematological Characteristics of Allogeneic Leukocyte-Poor Platelet-Rich Plasma - Salma Nadiyah; Resti Ariani; Awal Prasetyo (Jurnal Penelitian Inovatif, 2026)
Allogeneic PRP (Al-PRP) was platelet concentrate from voluntary donors as therapy. The composition within a PRP preparation other than platelets (PLT) may also include white blood cell (WBC) and red blood cells. The biochemical parameters as inflammatory markers such as platetet to white blood cell ratio (PWR) indices in a variety of medical conditions. Aims to investigate the effects of different storage temperatures and storage durations on the hematological characteristics of Al-LP-PRP. Methods: This pilot study used 3 different donors as source of allogenic PRP (a, b and c) with informed consent. The samples were three aliquots and stored at 22°C (room temperature), 4oC (refrigerator), and -20oC (deep freezer). The samples were observation by time analysis (1 day, 3 days, and 7 days). After storage, the parameters were assessed using Hematology Analyzer XP-100. PWR was defined as PLT divided by WBC. Result: The age of male donors were 34.67 ± 2.1 (mean ± SD). Platelet and WBC level were significant difference at storage conditions, whereas red blood cell levels did not differ significantly. WBC level had negative correlation to platelet to white blood cell ratio. Conclusion: Room-temperature storage was the most effective condition for preserving the hematological characteristics of allogeneic leukocyte-poor platelet-rich plasma (Al-LP-PRP). The findings of this pilot study provide preliminary evidence supporting the development of standardized storage protocols for future regenerative medicine applications, however, further validation in studies involving a larger sample size is needed.